Benchmarking technical efficiency of rice farms in Ghana: An empirical application of alternative production frontier approaches - Rebecca Owusu Coffie (The Central European Review of Economics and Management (CEREM), 2018)
Aim: In spite of investments in new technologies to improve upon rice production in Ghana, productivity levels are still low. It is therefore important to assess the efficiency of farmers and identify sources of inefficiency to develop policies to reduce inefficiencies. This paper aims to investigate the extent and drivers of technical efficiency of rice farmers in Ghana.Design/Research methods: Bias-corrected data envelopment and restricted single-stage stochastic frontier models are employed to examine the technical efficiency of farmers and its determinants. ~The data for empirical application come from a farm production survey comprising a total sample of 197 rice farmers from Ghana.Conclusions and findings: The analyses revealed on average, farmers are about 65% technically efficient. This result indicates that there is a potential to improve upon technical efficiency of farmers by about 35% within the existing state of resources and technology. Furthermore, the drivers of technical efficiency were identified as food insecurity status and membership of farmer based organisation. Specifically, the results show an inverse relationship between food insecurity status and technical efficiency; where higher levels of food insecurity are associated with lower levels of technical efficiency. Also, membership of farmer based organisation increases technical efficiency of farmers. Contrary to previous studies, non-farm income and credit access were not identified as significant drivers of technical efficiency among the sampled farmers. On the basis of the findings, policies should aim at reducing food insecurity among farmers and encouraging membership of farmer based organisations.Originality/value of the article: This paper provides evidence-based information on the extent of technical efficiency of rice farmers in Ghana and suggests measures for technical efficiency improvements.
Keywords: Q1; Q12; 330; Technical efficiency; rice production; food insecurity; new technologies; bias-corrected data envelopment